Mulberry leaf extract improves non-specific immunity and antioxidant capacity of largemouth bass (Micropterus salmoides) fed a high-starch diet - Tingsen, Jing; Hui, Luo; Junwa, Huang; Zhe, Li; Yu, Li; Honghao, Jin; Xinxi, Zou; Zhenlin, Ke; Wenbo, Sun; Mengdan, Hou; Huijun, Yang; Hua, Ye (Frontiers in Marine Science, 2022)
A 70-day experiment was carried to investigate the effects of mulberry leaf extract (MLE) on growth, proximate compositions, antioxidant and plasma biochemical parameters and nonspecific immune indices of largemouth bass, Micropterus Salmoides fed high starch diet. 280 largemouth bass (initial body weight: 68.00 ± 0.19g) were randomly fed seven diets: basal-starch diet (8.88% starch, BSD), high-starch diet (11.40% starch, HSD), and HSD diets supplemented with 0.05%, 0.10%, 0.20%, 0.50% and 1.00% MLE (MLE1, MLE2, MLE3, MLE4, MLE5, respectively). The results indicated that HSD and MLE did not significantly affect the growth performance of largemouth bass during the experimental period compared with BSD, but the supplementation of more than 0.20% (MLE3, MLE4, MLE5) MLE could significantly decrease the HSI and 1.00% (MLE5) MLE could significantly decrease the VSI (P < 0.05). The moisture in whole-body of fish fed HSD was significantly decreased (P < 0.05), while lipid of the whole body significantly increased of HSD compared with the BSD group (P < 0.05). Compared to HSD, MLE supplementation significantly decreased the content of moisture and lipid in the whole body (P< 0.05). The supplementation of more than 0.20% MLE (MLE3, MLE4, MLE5) significantly decreased the moisture in muscle (P < 0.05). The supplementation of 1.00% MLE significantly decreased the content of hepatic glycogen and muscle glycogen (P < 0.05). The malondialdehyde (MDA) content of the HSD group was significantly increased compared BSD (P < 0.05), whereas more than 0.10% (MLE2, MLE3, MLE4, MLE5) MLE significantly decreased the content of MDA (P < 0.05). Additionally, total antioxidant capacity (T-AOC), catalase (CAT) and glutathione peroxidase (GSH-Px) activities of MLE5 were significantly increased compared with the HSD group (P < 0.05). The content of complement3 (C3) and globulin albumin (GLB) in the plasma of the HSD group was significantly lower than BSD treatment (P < 0.05). The plasma C3, glucose (GLU) in MLE3, MLE4 and MLE5 groups were significantly higher than the HSD group (P < 0.05). Overall, these findings suggested that MLE could improve antioxidant capacity, immune function, and glycolipid metabolism, alleviating the negative effects of M. salmoides high-starch diet.